Analisis Jenis Kesalahan Mahasiswa Dalam Pembuktian Matematis Pada Mata Kuliah Analisis Real - Rusi Ulfa Hasanah; Devi Tri Lestari; Putri Anggraini; Nabila Utami (Universitas Maritim AMNI Semarang, 2024)
Mathematical proof is an important aspect in real analysis courses but is often a challenge for students. This research aims to analyze the types of errors that students often make in mathematical proofs in real analysis courses. The research method uses library research to explore the background, objectives, methods, findings and implications of the problem. The results of the analysis show that logical errors, conceptual errors, notation and writing errors, and heuristic thinking errors are the most common. These findings imply the need to develop more effective learning strategies to help students overcome difficulties in mathematical proofs. By understanding the types of errors that frequently occur, instructors can design learning methods that better suit students' needs.